PENGARUH PERENCANAAN AUDIT, PEER REVIEW, DUE PROFESSIONAL CARE, DAN AKUNTABILITAS TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK (KAP) DI KOTA DENPASAR - Ni Putu Evayanti; Kadek Dewi Padnyawati; Putu Nuniek Hutnaleontina (Hita Akuntansi dan Keuangan, 2021)
This study entitled the effect of audit planning, peer review, due professional care, and accountability on audit quality at the Public Accounting Firm (KAP) in Denpasar City. KAP is an institution that has a permit from the Minister of Finance as a forum for public accountants to carry out their work. The purpose of this study was to analyze the effect of audit planning, peer review, due professional care, and accountability on audit quality at KAP in Denpasar City. This research was conducted at KAP in Denpasar City which is listed in the Directory of the Indonesian Institute of Public Accountants in 2019. The number of samples in this study were 63 auditors who worked for KAP in Denpasar City. The sample in this study was determined by purposive sampling method. Data obtained through a questionnaire with the data analysis technique used is multiple linear regression analysis using SPSS. The results showed that audit planning had a positive and significant effect on audit quality with a significance value of 0.022 <0.05. Peer review has a positive and significant effect on audit quality with a significance value of 0.024 <0.05. Due professional care has a positive and significant effect on audit quality with a significance value of 0.046 <0.05. Accountability has a positive and significant effect on audit quality with a significance value of 0.040 <0.05. The results of the Determination analysis show that the percentage of Audit Planning (X1), Peer Review (X2), Due Professional Care (X3), and Accountability (X4) on Audit Quality (Y) is 0.664 x 100% = 66.4% with the remaining 33, 6% is influenced by other variables outside the research.